2001
DOI: 10.1210/endo.142.9.8384
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Dependent Regulation of Ovarian Pituitary Adenylate Cyclase-Activating Polypeptide mRNA Levels by GnRH in Cultured Rat Granulosa Cells

Abstract: The present study was designed to test whether GnRH regulates pituitary adenylate cyclase-activating polypeptide mRNA levels in a stage-dependent manner during follicle development in the rat ovary. The granulosa cells of preovulatory and immature follicles obtained from PMSG- and estrogen-treated rats, respectively, were cultured in serum-free conditions in the presence of various hormones. GnRH receptor mRNA expression was detected in both preovulatory and immature granulosa cells and was down-regulated by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Previous studies and the present work identified high/ovulatory levels of gonadotropins as a physiological regulator of PACAP in preovulatory follicles (Gras et al 1996, Lee et al 1999. Results from granulosa cell cultures also indicated that the expression of PACAP transcripts is increased by the treatment with LH, FSH, GnRH, FSK and cAMP analogs (Lee et al 1999, Park et al 2001, Wang et al 2003. The present study confirms that the expression of PACAP was significantly stimulated by FSK treatment or cPKA overexpression, but inhibited by PKA inhibitor H89 treatment or PKI overexpression, suggesting that activation of adenylyl cyclase/cAMP/ PKA induces PACAP expression in bovine granulosa cells.…”
Section: Regulation Of Pacap In Ovarian Folliclessupporting
confidence: 69%
“…Previous studies and the present work identified high/ovulatory levels of gonadotropins as a physiological regulator of PACAP in preovulatory follicles (Gras et al 1996, Lee et al 1999. Results from granulosa cell cultures also indicated that the expression of PACAP transcripts is increased by the treatment with LH, FSH, GnRH, FSK and cAMP analogs (Lee et al 1999, Park et al 2001, Wang et al 2003. The present study confirms that the expression of PACAP was significantly stimulated by FSK treatment or cPKA overexpression, but inhibited by PKA inhibitor H89 treatment or PKI overexpression, suggesting that activation of adenylyl cyclase/cAMP/ PKA induces PACAP expression in bovine granulosa cells.…”
Section: Regulation Of Pacap In Ovarian Folliclessupporting
confidence: 69%
“…PACAP has been shown to have several functions in follicular development. PACAP is expressed stage‐specifically in granulosa cells of large mature follicles before ovulation, but weaker expression has also been shown in the wall of immature antral and pre‐antral follicles 19, 32, 33. PACAP receptors have also been demonstrated in developing follicles 34–36.…”
Section: Discussionmentioning
confidence: 99%